Comparative study of R134a and R744 driven solar assisted heat pump systems for different applications - Baradey, Yehya; Hawlader, Mohammad Nurul Alam; Ismail, Ahmad Faris; Hrairi, Meftah (IOP Publishing, 2016)
A solar assisted heat pump (SAHP) system is considered in this study where space cooling, water heating, drying and desalination are carried out using solar energy, ambient energy and the waste heat available from air conditioning system. The integration of different applications with SAHP system leads to many benefits, but the most significant is the energy conservation issue where the prices of fossil fuels are increasing. In recent years, researches have been conducted worldwide to improve the performance of these systems. These systems usually use synthetic refrigerant, such as R134a, which contributes to many atmospheric problems. Currently, embracing natural refrigerants, such as, carbon dioxide in SAHP has become a trend specifically after Kyoto agreement to reduce global warming and improve the performance of SAHP systems. In this paper, comparative study using R134a and R744 in SAHP systems have been considered. The comparison includes the most significant results of previous work relevant to this issue, and the thermo physical properties of the two refrigerants when used in SAHP.